ACUTE EFFECTS OF ANKLE WEIGHT LOADING ON REGIONAL ACTIVITY OF RECTUS FEMORIS MUSCLE AND LOWER-EXTREMITY KINEMATICS DURING WALKING IN OLDER ADULTS (Kinesiology, 2023)
Ankle weight loading is a straightforward and easily applicable method to increase the physiological burden during walking in older adults. The current study investigated the acute effects of ankle weight loading on the regional activity of rectus femoris (RF) muscle and lower-extremity joint angles during walking in twenty-nine healthy older adults. Neuromuscular activities of proximal (RFP) and distal (RFD) regions of the RF into averaged rectified values (ARV) and kinematics of left lower extremities were measured during walking with and without ankle weight on a treadmill using surface electromyography (EMG) and motion capture, respectively. Significant differences in normalized ARV between RFP and RFD with ankle weight loading were found in longer periods of the stance phase (30-55 and 5-15%) and swing (70-90 and 95-100%) phases compared to without weight condition (30-40, 50, and 75-85%) (p